Clonal BRAF mutations in melanocytic nevi and initiating role of BRAF in melanocytic neoplasia - Yeh, Iwei; Deimling, Andreas von; Bastian, Boris (Journal of the National Cancer Institute, 2013)
BRAFV600E mutations are frequent in melanomas originating from intermittently sun-exposed skin and also in common acquired melanocytic nevi, suggesting that BRAF mutation is an early event in melanocytic neoplasia. All neoplastic melanocytes within such a nevus would be expected to carry the BRAF mutation, and thus we evaluated the frequency of cells with BRAFV600E mutations within acquired nevi by droplet digital polymerase chain reaction. In BRAF-mutant nevi the number of BRAF mutant alleles equaled the number of wild-type (WT) alleles in the neoplastic cell population, consistent with a fully clonal heterozygous BRAF mutation. The allelic ratio of BRAFV600E to BRAFWT in the eight VE1-positive nevi, adjusted for degree of stromal contamination, ranged from 0.84 to 1.12 with an average ratio of 1.01. This was confirmed by immunohistochemistry with an antibody specific for BRAFV600E, which uniformly labeled the neoplastic cells without any evidence of heterogeneity. We found BRAFV600E mutations in the melanocytic nevi to be fully clonal, strongly suggesting that BRAF-activating mutations typically are early initiating events in melanocytic neoplasia.